Gender Characteristics on Gaze Movement in Situation Awareness - Yejin Lee; Kwangtae Jung; Hyunchul Lee (Applied Sciences, 2021)
In large systems, such as nuclear power plants, the operator’s situation awareness is vital to the system’s safety. Since gaze movement is closely related to situation awareness, various studies have evaluated it through gaze movement. The number of female workers is increasing even in large systems, such as nuclear power plants, so it is relevant to compare and analyze the situation awareness and gaze movement characteristics of men and women. In this study, an experiment was conducted to compare and analyze men’s and women’s situation awareness and gaze movement characteristics by making a simulator for emergency scenarios in nuclear power plants. Gaze entropy was used as a measure to indicate gaze movement, while the Situation Awareness Rating Technique (SART) was utilized to measure situation awareness. A total of 20 engineering college students (10 male, 10 female) participated in the experiment. Loss of coolant accident (LOCA), steam generator tube rupture (SGTR), steam line break (SLB), and loss of voltage (LOV) were the nuclear power plant accident situations used as task scenarios for the experiment. For all accident scenarios, the SART score did not show a significant difference between men and women. Shannon entropy, dwell time entropy, and heat map entropy did not show a significant difference between men and women, but Markov entropy was found to be significantly higher in women. In conclusion, there was no significant difference between men and women in awareness of accident situations. In addition, there was no significant difference between men and women in the ratio of viewing the necessary information elements in the situation awareness process. However, it was found that women had more gaze movements between necessary information elements than men.